Superconducting MoN thin films prepared by DC reactive magnetron sputtering for nanowire single-photon detectors. (2nd February 2021) - Hallett, Lily; Charaev, Ilya; Agarwal, Akshay; Dane, Andrew; Colangelo, Marco; Zhu, Di; Berggren, Karl K
Abstract: We present a comprehensive study of molybdenum nitride (MoN) thin film deposition using direct current reactive magnetron sputtering. We have investigated the effect of various deposition conditions on the superconducting and electrical properties of the films. Furthermore, we have shown that meander-shaped single-photon detectors made from 5 nm MoN films have saturated quantum detection efficiency at the telecom wavelength of 1550 nm. Our results indicate that MoN may be a material of interest for practical applications of low-temperature superconductors, including single-photon detectors and transition-edge sensors.